Strategies in the fabrication of modified graphene nanomaterials: prospects in the electrochemical sensing of biomolecules and anticancer effects - Geetha Bai, Renu (2017)
Being one of the highly explored nanomaterials, graphene and derivatives are in the limelight of scientific research. The quest of mass production of graphene in a fast, eco-friendly and economical way lead to different greener synthesis approaches with reduced risk and harm to the environment. Here through this investigation, different greener approaches in the preparation of graphene and its derivatives were analysed. Moreover, the biocompatibility of the product is analysed for ensuring the safety while introducing as a biomaterial to a living system.